Cyanide-Resistant Respiration in Neurospora crassa - Lambowitz, Alan M. (1971)
Cell respiration in wild type and poky was studied as part of a long-term investigation of cyanide-resistant respiration in Neurospora. Respiration in wild type proceeds via a cytochrome chain which is similar to that of higher organisms; it is sensitive to antimycin A or cyanide. Poky, on the other hand, respires by means of two alternative oxidase systems. One of these is analogous to the wild-type cytochrome chain in that it can be inhibited by antimycin A or cyanide; this system accounts for as much as 15% of the respiration of poky f(−) and 34% of the respiration of poky f(+). The second oxidase system is unaffected by antimycin A or cyanide at concentrations which inhibit the cytochrome chain maximally. It can, however, be specifically inhibited by salicyl hydroxamic acid. The cyanide-resistant oxidase is not exclusive to poky, but is also present in small quantities in wild type grown under ordinary circumstances. These quantities may be greatly increased (as much as 20-fold) by growing wild type in the presence of antimycin A, cyanide, or chloramphenicol.